The Vanishing Public Monopoly - Levy, Daniel C. (International Higher Education, 2018)
A significant aspect of the massive growth of private higher education is the near disappearance of public monopoly. Almost all countries now have both public and private sectors of higher education. The decline of public monopoly has been notable for decades, the demise of Communism providing the most impactful moment. The remaining monopoly presence is mostly in small systems, often with rather left-leaning political regimes. In several of these countries, activity to end public monopoly is already underway.